Analysis of glass ceiling and sticky floor effects for gender wage gap in Malaysian labour market - Rahmah Ismail,; Chung, Khain Wye; Nur Sabrina Mohd Palel, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Most past studies of gender wage differentials estimate wage models using the entire sample for different gender groups. The estimated coefficients are then used in wage decomposition formula to identify the contribution of variables to the wage gap. However, quantile regression is preferred nowadays as it allows the regressors to be associated with the shape of wage distribution, whereby the glass ceiling and sticky floor effects can be identified. This paper attempts to examine the extent to which the glass ceiling and sticky floor effects exist across wage distribution in the Malaysian labour market. The analysis is based on 1263 workers data in the services and manufacturing sectors surveyed in 2015. The results demonstrate that the gender wage gaps are larger towards the lowest wage distribution, a finding that is consistent with the existence of sticky floor effect. Besides, the gender earnings gap is lower between 25th and 50th percentiles, but increases at the 75th percentile and reaches the highest at the 90th percentile reflecting the existence of glass ceiling effect.